Multicenter registry and test bed for extended outpatient hemodynamic monitoring: the hemodynamic frontiers in heart failure (HF2) initiative - Heywood, J. Thomas; Munshi, Kartik; Jordan, Timothy; Muse, Evan; Fudim, Marat; Sauer, Andrew J.; McDermott, Margaret; Shah, Hirak; Bhimaraj, Arvind; Khedraki, Rola; Robinson, Monique R.; McCann, Patrick; et al. (Frontiers in Cardiovascular Medicine, 2023)
The registry was approved by the institutional review board (IRB) at all participating institutions with required data use agreements. Institutions report data into the electronic registry database using REDCap, housed at KUMC. Results This initial data set includes 254 patients implanted from the start of 2019 until May 2023. At time of device implant, the cohort average age is 73 years old, 59.8% are male, 72% have NYHA Class III HF, 40% have left ventricular ejection fraction (LVEF) <40%, 35% have LVEF > 50%, mean BNP is 560 pg/mL, mean N-Terminal pro-BNP (NTproBNP) is 5490 pg/mL, mean creatinine is 1.65 mg/dL. Average baseline hemodynamics at device implant are right atrial pressure (RAP) of 11mmHg, pulmonary artery systolic pressure (PASP) of 47 mmHg, pulmonary artery diastolic pressure (PADP) 21 mmHg, mean pulmonary artery pressure (mPAP) of 20 mmHg, pulmonary capillary wedge pressure (PCWP) of 19 mmHg, cardiac output (CO) of 5.3 L/min, and cardiac index (CI) of 2.5 L/min/m 2 . Conclusion A real-world registry of patients implanted with a PAP sensor enables long-term evaluation of hemodynamic and clinic outcomes in highly-phenotyped ambulatory HF patients, and creates a unique opportunity to validate and test novel diagnostic and therapeutic approaches to HF.